Violent, political, and administrative repression of the Chinese minority in Indonesia, 1945-1998 - Heidhues, Mary Somers (Wacana, Journal of the Humanities of Indonesia, 2017)
Since Indonesian independence, its Chinese minority has been a victim of violent outbreaks, but also of restrictive policies arising from politics and administrative measures. From about 1957, with the closure of Chinese-language schools and subsequent regulations about expression of Chinese culture, many speak of the "erasure" of that culture through such restrictions. Violent anti-Chinese outbreaks have proceeded from the Indonesian Revolution and the presidency of Soekarno (especially the so-called "PP-10" measures against Chinese rural traders) to the era of Suharto, which began with the 1965-1967 anti-Communist massacres and their effects on ehtnic Chinese and came to an end with the provocation of violence against ethnic Chinese in major Indonesian cities. This paper also discusses the reactions to these waves of anti-Chinese measures: rejection, flight, but also countermeasures in the form of political activity. In the years since Reformasi, as attacks on them have subsided, many Chinese Indonesians have chosen to emphasize their participation in Indonesian history and their positive contributions to Indonesian culture.